Creatine supplementation--Part I: performance, clinical chemistry and muscle volume - Kamber, M.; Koster, M.; Kreis, R.; Walker, G.; Boesch, C.; Hoppeler, H. (Medicine & Science in Sports & Exercise, 1999)
Purpose: Our purpose was to study the effects and side effects of creatine (Cr) supplementation on high-intensity, short-term muscle work, on biochemical parameters related to Cr metabolism in blood and urine, and on muscle volume of the lower limb muscles. Methods: A cycling ergometer was used in a double-blind, cross-over study on 10 well-trained male physical education students to measure physical performance with 10 repetitive ergometer sprints (6-s duration, 30-s rest) before and after supplementation (5 d, 20 g·d-1, washout period 61 ± 8 d, mean ± SEM, minimum 28 d) with Cr or placebo. Before and after supplementation, blood and urine were taken and the muscle volume of the lower limb was determined by magnetic resonance imaging (MRI). Results: A significant (P < < 0.05) increase in performance (+ 7%) at the end [4-6 s] of the later sprints (4-7 and 8-10) was observed combined with a lower production of blood lactate (-1 mmol·L-1) with Cr supplementation. The concentration of Cr was increased significantly in urine (P < 0.001) and serum (P = 0.005), whereas creatinine (Crn) was increased in serum (P < 0.001). Crn in urine and Crn clearance did not change significantly with Cr intake. There were no significant changes in the analyzed blood enzyme activities. A significant gain of body weight (pre-Cr 76.5 ± 1.7 kg to 77.9 ± 1.7 kg post-Cr) with Cr supplementation was measured, but no accompanying increase of muscle mass in a limited volume of the lower limb was observed by MRI. Conclusion: Cr supplementation is effective in improving short-term performance, and the methods used show no detrimental side effects with this supplementation protocol.